Extended scrapie incubation time in goats singly heterozygous for PRNP S146 or K222: An update after seven years - White, S; Schneider, D A; Reynolds, J O; O'Rourke, K I; Waldron, D F (Journal of animal science, 2016)
Scrapie is the transmissible spongiform encephalopathy of sheep and goats, and efforts to eradicate scrapie are underway in many countries worldwide. Goats may serve as a reservoir for scrapie and. to date, there has been no experimental inoculation confirming strong, lifelong genetic resistance in goats. Goats bearing the S146 or K222 amino acid substitution in the goat prion protein have been present in scrapie-exposed herds, but significantly underrepresented in disease cases. Furthermore, both of these variant proteins give low cell-free protein conversion efficiency to the disease form, PrPSc. To ensure consistent exposure among test subjects, we performed an oral scrapie challenge of goats singly heterozygous for either SI46 or K222. All commonhaplotype homozygous controls became clinically scrapie positive by an average of 24 mo postinoculation: in stark contrast, none of the SI46 and K222 heterozygotes have scrapie-positive lymphoid biopsy tests or confirmed scrapie at incubation times now approaching 7 yr or longer (P > 0.0001). Recent reports indicate detection of natural scrapie in less than five S146 and K222 heterozygotes. suggesting heterozygotes will not have complete resistance. However, the scrapie incubation times are now as long as or longer than many commercial operations keep goats for production piuposes. This suggests breeding goats singly heterozygous for S146 or K222 may reduce the probability of clinical scrapie during the productive life spans of many commercial goats. These results also suggest much longer relevant trace-back histories for goats of these genotypes in scrapie-eradication programs. Finally, these data support additional consideration of the potential scrapie-resistance present in homozygotes for these genotypes, since, to our knowledge, there have never been natural scrapie positives in homozygotes for either allele.